PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE (4E) DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA PEMBELAJARAN IPA BIOLOGI (SISWA KELAS VIIE SMP NEGERI 9 JEMBER TAHUN PELAJARAN 2013/2014) - Margi Eldayanti; Puju Astuti; Sulifah Aprilya Hariani (BIOEDUKASI, 2016)
One of learning models that can involve the active student in the learning process is Learning Cycle (4E). The results obtained by applying the Learning Cycle (4E) method is the increase of the activity of learning, in pre-cycle the result obtained 53,14% (less active criteria) increased to 62,08% (quite active criteria) in tha first cycle and in the second cycle increased to 75,38% (active criteria). The results obtained in the classical learning increased in pre-cycle (6.67%), to the first cycle (43.33%) and the second cycle (70%), then the aspects of affective is 75.33% in the first cycle, and increased in the second cycle to 77.46%. In the psychomotor aspects it raise to 71,67% that increase in the first cycle meeting 2 and increased to 77,5% in the second cycle of the meeting 2. So we can know that Learning Cycle (4E) method can improve the activities and the outcome of learning process based on the results. Keywords: student activities, the result of learning, Learning Cycle (4E) model.